Numerical modeling of granular pile-anchor foundations (GPAF) in reactive soils - Ismail, M.; Shahin, Mohamed (J Ross Publishing Inc, 2012)
Laboratory and field studies have shown that granular pile-anchor foundations (GPAF) are a promising foundation system that can be used to reduce the detrimental effects of reactive soils. This paper presents results from finite element analyses undertaken on granular pile-anchor foundations in a reactive soil using PLAXIS software. The study investigated the ability of a single pile to resist forces induced by both heave and shrinkage. The results confirmed the efficiency of the granular pile-anchor foundations in resisting heave induced by moisture gain. However, in order to resist shrinkage, the GPAF system has to be reinforced with geofabric to assist resisting bulging of the granular pile into the surrounding soil. The analyses showed that success of the GPAF in heave resistance may be adversely influenced by the high stiffness of the interface, which requires only small relative movement to mobilize full resistance. The efficiency of the GPAF system increases with the ratio between the pile diameter and supported footing. Using a group of piles instead of a single pile under a footing can reduce the efficiency of the GPAF system.